DEVELOPMENT OF JAVANESE SCRIPT APPLICATION TO INCREASE LEARNING MOTIVATION OF ELEMENTARY SCHOOL STUDENTS - Muna, Shofiyatul; Buchori, Achmad; Wardani, Theodora Indriati (Schola, 2023)
This research, which aims to increase the learning motivation of elementary school students, was conducted at Loireng State Elementary School. Research and Development (R&D) method were used to develop this Javanese script application. The subjects in this study were grade 5 (five) students at SDN Loireng. The results of motivation before and after using the Javanese script application amounted to 65% and 98%, it was concluded that the learning motivation questionnaire obtained the results of 46% of students in the moderate category. In normality testing, the results of the Asymp.Sig. (2-tailed) significance value of 0.000 < 0.05, so the data is not normally distributed. In the Wilcoxon Signed Rank Test test, it is known that Asymp.Sig. (2-tailed) is 0.000 because the value of 0.000 < 0.05. So it can be concluded that there is an influence on increasing the learning motivation of grade 5 (five) students of Loireng State Elementary School.